Library Service Innovation Trends During Covid-19 in Indonesia: A Systematic Literature Review - Anggelia, Rikka Poerna; Irawati, Indira (UI Scholars Hub, 2022)
The Covid-19 pandemic in Indonesia has forced all aspects of life to follow Covid-19 health protocols by reducing mobility so that physical contact can be minimized. Likewise, libraries must provide service innovations in order to reduce the physical contact and any risk to the virus transmission. The objective of this research is to identify trends and types of library service innovations in effort to confront Covid-19 pandemic in Indonesia. The method of this research is systematic literature review (SLR), which is a method that can be used to measure or identify a phenomenon or a question that involves and requires analysis of several literature resources. The results obtained from database search were found 24 literatures relevant to the topic of innovation trends in adjusting with the Covid-19 pandemic in Indonesia. Library innovation in the form of online library services dominates services in libraries and is also widely adapted. The types of library service innovations that are mostly carried out by libraries in Indonesia includes online circulation services with OPAC access through the website, the use of google forms, interaction of ask a Librarian with WhatsApp, Telegram, and Email. In the long term, this library innovation is expected to be able to serve and provide better library services, not only worthwhile during the pandemic.